PSO-GWO Optimized Fractional Order PID Based Hybrid Shunt Active Power Filter for Power Quality Improvements - Alok Kumar Mishra; Soumya Ranjan Das; Prakash K. Ray; Ranjan Kumar Mallick; Asit Mohanty; Dillip K. Mishra (IEEE Access)
This paper presents a Hybrid Shunt Active Power Filter (HSAPF) optimized by hybrid Particle Swarm Optimization-Grey Wolf Optimization (PSO-GWO) and Fractional Order Proportional-Integral-Derivative Controller (FOPIDC) for reactive power and harmonic compensation under balance and unbalance loading conditions. Here, the parameters of FOPID controller are tuned by PSO-GWO technique to mitigate the harmonics. Comparing Passive with Active Filters, the former is tested to be bulky and design is complex and the later is not cost effective for high rating. Hence, a hybrid structure of shunt active and passive filter is designed using MATLAB/Simulink and in real time experimental set up. The compensation process for shunt active filter is different from predictable methods such as (p-q) or ( ${i}_{d}-{i}_{q}$ ) theory, in which only the source current is to be sensed. The performance of the proposed controller is tested under different operating conditions such as steady and transient states and indices like Total Harmonic Distortion (THD), Input Power Factor (IPF), Real Power (P) and Reactive Power (Q) are estimated and compared with that of other controllers. The parameters of FOPIDC and Conventional PID Controller (CPIDC) are optimized by the techniques such as PSO, GWO and hybrid PSO-GWO. The comparative simulation/experiment results reflect the better performance of PSO-GWO optimized FOPIDC based HSAPF with respect to PSO/GWO optimized FOPIDC/CPIDC based HSAPF under different operating conditions.